Spontaneous emission in the presence of quantum mirrors - Kanu Sinha; Jennifer Parra-Contreras; Annyun Das; Pablo Solano (New Journal of Physics)
Arrays of atoms coupled to waveguides can behave as mirrors. We consider an array of three-level atoms, with one excited and two ground levels, assuming one of the ground levels to be decoupled from the other two. Preparing the atoms in the coupled or decoupled ground state leads to reflection or transmission of the guided electromagnetic field; a superposition of the two ground states thus corresponds to a coherent superposition of mirror-like and transparent boundary conditions. We analyze the spontaneous emission of an excited two-level atom in the presence of such a quantum mirror , and inside a cavity formed by quantum mirrors, demonstrating that the resulting dynamics of the excited atom can exhibit exotic features, e.g. a superposition of Rabi cycle and exponential decay. Our results pave the way for exploring quantum electrodynamics (QED) phenomena in a paradigm wherein boundary conditions can exhibit quantum superpositions and correlations.